2009
DOI: 10.2500/ajra.2009.23.3357
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Degranulation Patterns in Nasal Polyposis: An Ultrastructural Study

Abstract: Cytolysis and PMD are the principal degranulation modes of eosinophils in nasal polyposis-apoptosis being very infrequent. Nasal polyposis shows a correlation between eosinophil degranulation mode and the clinical and radiological stage and the degree of tissue eosinophilia of the case of origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 16 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…More than 20 years ago, Hellquist reported that the edematous eosinophilic type accounted for 86% of all polyps in Sweden. Therefore, eosinophils are probably the most common and important inflammatory cells in the pathogenesis of polyps . It has been well accepted that 1 of the most common histological features of nasal polyps is eosinophilia in the mucosa and submucosa .…”
Section: Resultsmentioning
confidence: 99%
“…More than 20 years ago, Hellquist reported that the edematous eosinophilic type accounted for 86% of all polyps in Sweden. Therefore, eosinophils are probably the most common and important inflammatory cells in the pathogenesis of polyps . It has been well accepted that 1 of the most common histological features of nasal polyps is eosinophilia in the mucosa and submucosa .…”
Section: Resultsmentioning
confidence: 99%
“…13,52 Exocytosis is an uncommon in vivo eosinophil degranulation event, but can be observed during in vitro interaction of eosinophils with different parasitic helminths 72 and environmental fungi 73 or after in vitro stimulation with high concentration of TNF-. 9 Cytolysis and PMD are the most frequent modes of eosinophil degranulation in vivo, being well documented in numerous human diseases such as nasal polyposis, [76][77][78] allergic rhinitis, 77,79 atopic dermatitis, 80 asthma, 77 ulcerative colitis, 77 Crohn's disease, 77 shigellosis, 81 cholera, 82 gastric carcinoma, 83 and eosinophilic esophagitis. 59 Interestingly, human eosinophils can show different degranulating patterns in vivo, in response to a specific eosinophilic disease or condition.…”
Section: Eosinophil Specific Granules Are Membranous Compartmentalizementioning
confidence: 99%
“…The pathophysiology of tissue eosinophilia is incompletely known, but Th2 cytokines including IL-5 and eotaxins play an indispensable role in eosinophil-selective accumulation, similar to other allergic diseases [12, 18]. Of note, approximately 30 % of tissue eosinophils in CRSwNP exhibit ultrastructural evidence of cytolysis [19]. …”
Section: Lessons From Chronic Rhinosinusitis: Pathogenesis Of Eosinopmentioning
confidence: 99%